2016
DOI: 10.2961/jlmn.2016.02.0010
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Photography of Laser Induced Forward Transfer (LIFT) of Single and Double-layered Transfer Layers for Single Cell Transfer

Abstract: In this study, we worked on the formation of micro through holes in multi-component glass substrates using laser-assisted etching, in which mixed aqueous solutions of hydrofluoric acid (HF) and nitric acid (HNO 3 ) were used for the etching. Glass samples modified by femtosecond laser irradiation were immersed for 10 minutes in aqueous solutions containing 2% HF and between 0 and 32% HNO 3 . The subsequent optical microscope observations and measurements showed that the highest etch selectivity, which was 21, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In addition to the parameters of laser exposure, the transfer process is also affected by the hydrogel parameters (viscosity, density, and surface tension)[ 16 , 33 ] and its thickness on the ribbon. The variation of these parameters allows changing the jetting dynamics and droplet formation[ 15 ] and achieving the optimal transfer regime with the formation of a stable jet without spraying[ 14 ], the formation of hydrogel droplets of the required volume[ 15 ], and the absence of unnecessary shock stresses on the transferred objects[ 13 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the parameters of laser exposure, the transfer process is also affected by the hydrogel parameters (viscosity, density, and surface tension)[ 16 , 33 ] and its thickness on the ribbon. The variation of these parameters allows changing the jetting dynamics and droplet formation[ 15 ] and achieving the optimal transfer regime with the formation of a stable jet without spraying[ 14 ], the formation of hydrogel droplets of the required volume[ 15 ], and the absence of unnecessary shock stresses on the transferred objects[ 13 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various other cell types, both carcinomatous and normal, show high viability, irrespective of the laser absorbing layer utilized [ 33 , 45 , 46 , 47 ]. Following printing, cell viability remains between 80 to 90%, or even close to 100% [ 20 , 44 , 48 , 49 , 50 ]. Moreover, all these studies show that the cells recover and start to proliferate normally within a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…During LIFT printing, three jetting regimes are usually described: the subthreshold, well-defined jetting, and plume regimes. It has also been demonstrated that the cell-printing deposition and the cell viability depend on jet dynamics and the jet impact with the receiver substrate, which are controlled by the rheological properties (viscosity, density, and surface tension) [32,33], and by the distance between the donor and the receiving substrate [34][35][36].…”
Section: Introductionmentioning
confidence: 99%